Hulu Kedah Dialect: A New Classification (Jurnal Bahasa, 2024)
This paper discusses the Malay dialect spoken in Baling, Kedah. The Malay dialect in this area is perceived by local speakers as being unique and different compared to the standard Kedah Malay dialect. Due to the existence of such a notion, a series of visits were made to Baling to collect data of its dialect. The purpose is to answer two basic questions in diachronic dialectology, namely: (i) what are the phonological features of the Malay dialect in Baling that differentiates it from standard Kedah Malay and other Malay dialects? (ii) What is the relationship between the said dialects? To answer this question, the researcher used the interview method by utilizing up to 643 lexical items in the corpus, including conversation recordings. The collected data was then analysed using a diachronic dialectology framework that focuses on description of shared innovation and retention, and also dialect comparison. The shared innovation and retention of phonological features is for the purpose of classification. Some phonological innovation and retention prove two things. Firstly, the Baling Malay dialect is distinct from the Malay dialect branch of the Northern Peninsula. In other words, this dialect is not a "subdialect" of the standard Kedah Malay dialect. Secondly, since this Malay dialect is distinct from the said branch and shares similarities with other Malay dialects around it, the Baling dialect forms its own branch. This branch is called the hulu dialect branch of the Northern Peninsula. It comprises the dialects spoken by communities living in the upstream areas of Kedah, including Baling, Sik, Kuala Nerang, Padang Terap and the upstream area of Northern Perak. Besides linguistics, the familiar relationship in this dialect branch can also be strengthened with historical and sociological evidence. An important implication of the findings of this paper is the existence of a new branch in the Malay dialect of the Northern Peninsula that should be formally raised in the dialect classification of Peninsular Malaysia.Keywords: Dialectology, Hulu Kedah Malay, diachronic phonology, classification, innovation, retentionFull text: PDF